2021
DOI: 10.1111/echo.15011
|View full text |Cite
|
Sign up to set email alerts
|

Relation of p ‐ wave dispersion with presystolic a ‐ wave and aortic valve sclerosis in asymptomatic subjects

Abstract: It is well known that prevention is easier than cure. Constantly, scientific and technological developments continue to increase and it enables us new diagnostic and therapeutic methods. Prevention is also important for in the most common cause of persistent arrhythmiaatrial fibrillation (AF), to gain both medical and economic benefits. Studies have shown that atrial fibrillation is underdiagnosed and not adequately treated. Arrhythmia-atrial fibrillation is associated with cardiovascular and thromboembolic ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Our findings are similar to other studies showing that other significant predictors, such as DM, HT and HPL in particular, is also associated with AVS [2,10].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are similar to other studies showing that other significant predictors, such as DM, HT and HPL in particular, is also associated with AVS [2,10].…”
Section: Discussionsupporting
confidence: 92%
“…Aortic valve sclerosis (AVS) is defined as the thickening of the aortic valve without a hemodynamically significant obstruction of the left ventricular outflow [1]. Several studies have shown that age, diabetes mellitus (DM), hypertension (HT) and hyperlipidaemia (HPL) are risk factors for AVS [2]. AVS includes multiple pathological similarities to the atherosclerotic process and the prognostic value of AVS is explained by its strong relationship to atherosclerotic risk factors [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical consequences of having a presystolic wave are studied by Joshi et al [1], who found that in patients with low EF, the absence of the wave was associated with higher major adverse cardiac effects. The only study to evaluate the direct relationship between systemic hypertension and presystolic wave is conducted by Akyüz et al, [19] which showed a positive relationship in office blood pressure measurements. Our findings were consistent with previous studies in terms of associations of age, mitral inflow a wave and LVH.…”
Section: Discussionmentioning
confidence: 99%